Managerial Team Selection Strategy Based on Trust, Transparency, and Transformation in Driving Economic Transformation at DANANTARA (Daya Anagata Nusantara) - Irawati, Ira; Aritonang, Rian Fajar; Abdurrahman, Ifham Azhar; Candra, Rosikh (Universitas Padjadjaran, 2026)
Danantara, as a state asset management institution, aims to build a sustainable economic foundation through the principles of meritocracy, transparency, and professionalism in its managerial selection process. This study analyzes the application of trust, transparency, and transformation principles in the selection of Danantara’s managerial team and their impact on the effectiveness of state asset management. A qualitative approach was employed, using in-depth interviews and document analysis. The principle of trust highlights the importance of mutual confidence among team members and stakeholders, which, according to Kramer and Tyler (1996), can accelerate decision-making and enhance collaboration. Transparency, as emphasized by Gierlich-Joas et al. (2020), involves open information sharing within organizations to strengthen accountability. Meanwhile, the transformation principle focuses on adaptability and innovation, aligning with Norman and Pahlawati’s (2024) findings on the role of adaptive leadership in sustainable transformation. The preliminary findings indicate that implementing these three principles fosters a competent management team and improves Indonesia’s competitiveness globally. This research contributes to the development of effective state asset management practices and enriches the literature on economic transformation, positioning Danantara as a new driver of national economic growth.